Income,iInequality, and poverty during the transition from planned to market economy - Milanović, Branko (Washington, D.C. : World Bank, 1998)
This book is about income, inequality, and poverty during the remarkable period of collapse of Communism and the "construction" of capitalism in eighteen formerly socialist countries. It covers a period of almost ten years, from the time of the early Gorbachevian reforms of 1987-88 to approximately 1996. The book was made possible by two almost simultaneous revolutions that took place in the late 1980s. The first was the collapse of Communism and the second was the opening up of information on income, inequality, and poverty, even in countries where for the better part of the last seventy years such information had been treated as a state secret
Includes index.
Includes bibliographical references (p. 221-232).
rpm 21/09/16
Loans
Keywords: Income distribution -- Europe, Eastern; Income distribution -- Former Soviet republics; Poverty -- Europe, Eastern; Poverty -- Former Soviet republics; Europe, Eastern -- Economic conditions -- 1989-; Former Soviet republics -- Economic conditions; Europe, Eastern; Former Soviet republics